Importance of nutrition and weight loss in motor neuron disease - Dupuis, Luc (Henry Stewart Talks, 2023)
Amyotrophic Lateral Sclerosis (ALS), ALS and weight loss, Progression of ALS, High-calorie diet, Hypothalamus in ALS, Melanin-concentrating hormone (MCH) neurons, Relationship between MCH neurons, ALS, and weight loss